2020
DOI: 10.1109/access.2020.3030090
|View full text |Cite
|
Sign up to set email alerts
|

IoT in the Wake of COVID-19: A Survey on Contributions, Challenges and Evolution

Abstract: The novel coronavirus (COVID-19), declared by the World Health Organization (WHO) as a global pandemic, has brought with it changes to the general way of life. Major sectors of the world industry and economy have been affected and the Internet of Things (IoT) management and framework is no exception in this regard. This article provides an up to date survey on how a global pandemic such as COVID-19 has affected the world of IoT technologies. It looks at the contributions that IoT and associated sensor technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(93 citation statements)
references
References 66 publications
0
92
0
1
Order By: Relevance
“…The synthons allow to envisioned the technologies that could help with the data acquisition of patients. Kunsch et al [ 12 ] showed how the dry cough, symptom more common in COVID-19 can be captured with environmental sound sensors with similar efficiency to on-body sensors. The result in sound saturation in the environmental sensor can be seen in Figure 2 , where it is shown how cough relates to other factors and can be detected in different ways.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthons allow to envisioned the technologies that could help with the data acquisition of patients. Kunsch et al [ 12 ] showed how the dry cough, symptom more common in COVID-19 can be captured with environmental sound sensors with similar efficiency to on-body sensors. The result in sound saturation in the environmental sensor can be seen in Figure 2 , where it is shown how cough relates to other factors and can be detected in different ways.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…IoT in particular was used and improved in order to solve the challenge of virus tracing, tracking and spread mitigation. Automatic thermometer scanners in public spaces or tracking apps for positive patients are some examples [ 12 ].…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, wireless sensors networks and wireless communications are already playing an important role in the era of Covid-19 (Saaed et al, 2020;Kamal et al, 2020;Ndiaye et al, 2020). The wireless communication technologies can be used to enable monitoring of the virus spreading, to enable healthcare automation, and to allow virtual education and conferencing.…”
Section: Mathematics Computer Science and Mechanicsmentioning
confidence: 99%
“…Abbott et al, 2020;Besenyő et al, 2020;Sahin et al, 2020;or Rezk et al, 2020). Thanks to the spread of Internet and information and communication technologies (ICT), it became the first pandemic to be followed, reported on and commented upon in real time (Ye, 2002;Ndiaye et al, 2020). It was due to the wide media coverage and information flow that it soon began influencing consumer behaviour by bringing fear and uncertainty and therefore deteriorating markets.…”
Section: Introductionmentioning
confidence: 99%